(untitled) (International Journal of Engineering and Computer Science, 2015)
In today’s world, a new device is being developed almost every day. All such devices need a device driver for them to be compatible with the PC (Personal Computer). The objective of this work is to design and develop a USB (Universal Serial Bus) driver for real time applications. The device driver designed in this work is a combination of Firmware and Software. Firmware is constituted by the codes written into the Master and Slave Microcontrollers. Software using VB (Visual Basic) code has been developed for the frontend computer system. An USB protocol has been used for this work. This explains the development of new application used in communication industries for connecting modems, routers, hubs etc. and also it provides an easy way to install and operate the devices. This is the latest technology and has wide range of application in the world today.